2019
DOI: 10.20546/ijcmas.2019.801.119
|View full text |Cite
|
Sign up to set email alerts
|

Floral Biology and Fruit Set of Mango (Mangifera indica L.) as Influenced by Different Chemicals

Abstract: Satna (M.P.) India, during 2016-17 and 2017-18 to study the response of different mango cultivars viz. Bombay Green, Dashehari and Langra to various chemicals namely potassium nitrate, potassium di-hydrogen orthophosphate, di-potassium hydrogen orthophosphate. The results of the experiment revealed that the per cent of bud swelling, panicle emergence and flowering shoot and length of panicle were higher with application of KH 2 PO 4 -1%+KNO 3 -1%. In case of cultivars, mango cv. Langra produced lengthier pani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[10][11][12] It is also cultivated in West Indies, Israel, California, and Algeria. 13 Jamun becomes a fully grown tree in 40 years and become usually 100 feet (30 m) tall. Jamun canopy expands up to 36 feet (11m) and its trunk diameter reaches up to 2-3 feet (0.6-0.9 m) (Figure 1).…”
Section: Botanical Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] It is also cultivated in West Indies, Israel, California, and Algeria. 13 Jamun becomes a fully grown tree in 40 years and become usually 100 feet (30 m) tall. Jamun canopy expands up to 36 feet (11m) and its trunk diameter reaches up to 2-3 feet (0.6-0.9 m) (Figure 1).…”
Section: Botanical Descriptionmentioning
confidence: 99%
“…Initially, the flowers are greenish-white that turn rose pink eventually. [11][12][13][14] The Jamun starts fruiting in clusters of a few to 10 or even 40 during summer, which becomes fully ripened in June-July. The fruits of Jamun are oblong or round and their size varies between 1/2 to 2 inches (1.2 to 5cm).…”
Section: Botanical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Singh et al [21] showed that spraying mango cultivars Bombay Green, Dashehari and Langra with a combination of 1% KNO 3 and 1% KH 2 PO 4 was excellent over other combinations of chemicals in improving the number of fruits set and fruits retained per tree when compared with the control where the trees were sprayed with water only. Experimental results of another study by Parauha and Pandey [8] indicated that foliar spray of 2% KNO 3 + 30 ppm gibberellic acid on the cultivar Amrapali gave better performance in fruit yield (14.70 kg/tree) than the control (7.91 kg/tree).…”
Section: Effect Of Potassium Nitrate On Number Of Fruits Set Per 20 P...mentioning
confidence: 99%